Biological and physical processes influencing sea ice, under‐ice algae, and dimethylsulfoniopropionate during spring in the Canadian Arctic Archipelago. Issue 6 (12th June 2014) - Galindo, V.; Levasseur, M.; Mundy, C. J.; Gosselin, M.; Tremblay, J.‐É.; Scarratt, M.; Gratton, Y.; Papakiriakou, T.; Poulin, M.; Lizotte, M.
Abstract This study presents temporal variations in concentrations of chlorophyll a (Chl a), particulate and dissolved dimethylsulfoniopropionate (DMSPp and DMSPd) in the sea ice and underlying water column in the Canadian Arctic Archipelago during the spring of 2010 and 2011. During both years, bottom ice Chl a, DMSPp and DMSPd concentrations were high (up to 1328 µg L−1, 15, 082 nmol L−1, and 6110 nmol L−1, respectively) in May and decreased thereafter. The release of bottom ice algae and DMSPp in the water column was gradual in 2010 and rapid (8 days) in 2011. Bottom brine drainage during the presnowmelt period in 2010 and a rapid loss of the snow cover in 2011 coinciding with rain events explain most of the difference between the 2 years. During both years, less than 13% of the DMSPd lost from the ice was detected in the water column, suggesting a rapid microbial consumption. An under‐ice diatom bloom developed in both years. In 2010, the bloom was dominated by centric diatoms while in 2011 pennates dominated, likely reflecting seeding by ice algae following the faster snowmelt progression induced by rainfall events in 2011. Both under‐ice blooms were associated with high DMSPp concentrations (up to 185 nmol L−1), but pennate diatoms showed DMSPp/Chl a ratios twice higher than centrics. These results highlight the key role of snowmelt and precipitation on the temporal pattern of ice‐DMSP release to the water column and on the timing, taxonomic composition, and DMSP content of phytoplankton under‐ice blooms in the Arctic.